Evaluation of RF interactions between a 3T birdcage transmit coil and transcranial magnetic stimulation coils using a realistically shaped head phantom. Issue 2 (23rd January 2020) - Navarro de Lara, Lucia I.; Golestanirad, Laleh; Makarov, Sergey N.; Stockmann, Jason P.; Wald, Lawrence L.; Nummenmaa, Aapo
Abstract : Purpose: Multichannel transcranial magnetic stimulation (TMS) 1 is an emerging technology that allows multiple sites to be stimulated simultaneously or sequentially under electronic control without movement of the coils. A multichannel TMS/MRI head coil array for 3 Tesla is currently under development to mitigate challenges of concurrent TMS/fMRI as well as enable potential new applications. The influence of the multichannel TMS system on the MR image quality and safety must be carefully investigated. Methods: A standard birdcage volume coil for 3 Tesla systems was simulated using a commercial numerical electromagnetic solver. Two setups, consisting of 1) a MR‐compatible TMS coil, and 2) a 3‐axis TMS coil array, were simulated to quantify changes in the transmit field B 1 + and the SAR. A realistically shaped homogeneous head model was used in the computations. Results: The stimulation coils produced enhancements and attenuations on the transmit field with effects greater than 5% up to 2.4 cm and 3.3 cm under the scalp for the MR‐compatible TMS coil and 3‐axis TMS coil array, respectively. The 10 g‐SAR distribution did not change significantly in either of the cases; however, the nominal SAR maximum locus was shifted between existing hot spots. Conclusion: The simulated B 1 + variations found near the TMS coils indicate the possibility of inducing sequence‐dependent image artefacts predominatly limited to the vicinity of the coil(s). However, we conclude that neither the MR‐compatible commercial TMS coil nor the 3‐axis TMS coil array siginificantly elevate SAR in the head or neck beyond accepted safety limits.